PARENTAL OVER-INDEBTEDNESS AND YOUTH CRIME IN SWEDEN: A NATIONWIDE REGISTER-BASED STUDY - Rojas, Yerko; Bäckman, Olof (International Journal of Child, Youth and Family Studies, 2024)
Very little is known about whether a child’s delinquency can be related to a parent’s economic problems in terms of financial indebtedness. This would seem to be an important research gap, not least at a time when the repercussions of the 2008 global financial crisis are still being felt by many people. This study concerned boys and girls born in 2002 who had a parent with a registration date for a debt in the Swedish Enforcement Authority register between 2016 and 2017 (n = 3,284). We determined whether the adolescents had been convicted of a crime during the 3-year period when they were 15 to 17 years old, and compared their records with a sample from the general Swedish population (n = 16,435). Results from logistic regressions show that children who, at age 15 to 17, had a parent with debt problems were approximately one and a half times more likely to be convicted of a crime than children who were unexposed to registered debts of parents (OR = 1.55), irrespective of other well-established criminogenic risk factors observed prior to the parent’s date of registration at the Enforcement Authority. The results provide support for the notion that financial challenges and problems with creditors may be an important proximate risk factor of delinquency.